1997
DOI: 10.1007/s004390050507
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of a third locus in X-linked recessive spastic paraplegia

Abstract: We have investigated a family with severe X-linked spastic paraplegia and assigned the disease locus to Xq11.2-q23 by linkage and haplotype analysis. This region harbors the gene coding for proteolipid protein, which is mutated in one of the two established forms of X-linked spastic paraplegia, i.e., SPG2. We have performed extensive mutation analysis of this gene. Our failure to detect a mutation in this family suggests a third locus in X-linked recessive spastic paraplegia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…However X-linked (SPG16, Steinmuller et al 1997) and autosomal recessive (SPG5, 24, 28) uncomplicated forms also occur (Hentati et al 1994;Hodgkinson et al 2002;Bouslam et al 2005). Ten loci for autosomal dominant "uncomplicated"/"pure" hereditary spastic paraplegia (ADPHSP) have been mapped, for eight of which the causative genes have been identiWed (OMIM): SPG3A (MN_606439; 14q11-q21; Atlastin), SPG4 (MN_604277; 2p22; Spastin), SPG6 (MN_ 600303; 15q11.1; NIPA1), SPG8 (MN_603563; 8q23-q24; KIAA0196), SPG10 (MN_604187; 12q13; KIF5A), SPG12 (MN_604805; 19q13), SPG13 (MN_605280; 2q24-34; Chaperonin 60), SPG19 (MN_607152; 9q33-34), SPG31 (MN_609139; 2p12; REEP1) and SPG33 (MN_610243, 10q24.2; ZFYVE27).…”
mentioning
confidence: 97%
“…However X-linked (SPG16, Steinmuller et al 1997) and autosomal recessive (SPG5, 24, 28) uncomplicated forms also occur (Hentati et al 1994;Hodgkinson et al 2002;Bouslam et al 2005). Ten loci for autosomal dominant "uncomplicated"/"pure" hereditary spastic paraplegia (ADPHSP) have been mapped, for eight of which the causative genes have been identiWed (OMIM): SPG3A (MN_606439; 14q11-q21; Atlastin), SPG4 (MN_604277; 2p22; Spastin), SPG6 (MN_ 600303; 15q11.1; NIPA1), SPG8 (MN_603563; 8q23-q24; KIAA0196), SPG10 (MN_604187; 12q13; KIF5A), SPG12 (MN_604805; 19q13), SPG13 (MN_605280; 2q24-34; Chaperonin 60), SPG19 (MN_607152; 9q33-34), SPG31 (MN_609139; 2p12; REEP1) and SPG33 (MN_610243, 10q24.2; ZFYVE27).…”
mentioning
confidence: 97%
“…The present family, as well as the pedigree K101 reported previously [Cambi et al, 1995], has a mild form of pure X-linked spastic paraplegia. However, the other two families [Lazzarini et al, 1997;Steinmü ller et al, 1997] have a severe complicated clinical picture. It will be interesting to know if these phenotypes may also represent allelic forms of the same gene(s) or if they are caused by nonallelic genetic heterogeneity.…”
Section: Discussionmentioning
confidence: 98%
“…A mutation in the PLP gene was found by Cambi et al [1996] in a family with pure X-linked spastic paraplegia, confirming that mutations in this gene may cause both pure and complicated forms. A third locus, more than 10 cM away from the PLP gene, was identified in a family with PelizaeusMerzbacher-like disease, but the gene product is still unknown [Lazzarini et al, 1997;Steinmü ller et al, 1997;Claes et al, 2000].…”
Section: Introductionmentioning
confidence: 98%
“…Recently, Steinmuller et al [1997] mapped a third X-linked SPG locus at Xq11.2-q23 in a family with the complicated form of the disorder. In the family that we studied, SPG is thought to have been caused by a breakpoint in Xq11.2 arising from rDNA insertion.…”
Section: Discussionmentioning
confidence: 99%
“…The gene of Xq28 codes for mutations in the L1 cell adhesion molecule gene in SPG1, whereas defects in the proteolipid protein (PLP) gene in Xq21 have been identified in SPG2 [Kobayashi et al, 1996]. In addition, recent studies have suggested the existence of a third gene locus for X-linked SPG, in a more proximal, pericentromeric region on the long arm of the X chromosome [Steinmuller et al, 1997]. We describe a family with pure SPG, lacking nystagmus or mental retardation, and characterized by rDNA insertion in Xq11.2.…”
Section: Introductionmentioning
confidence: 98%